(untitled) - Botello, Chris (Boston, 2008)
Graphic design professionals and design students alike are discovering the smart, sophisticated approach of the page layout software, Adobe InDesign. And they're mastering it with Adobe InDesign CS3 Revealed, a thorough overview of the latest release of the software. This highly visual book begins by covering the workspace and other fundamental concepts. Each subsequent chapter delves into new features, offering more in-depth coverage as the book progresses. With new material on the improved interface and features of CS3, this edition retains its step-by-step tutorials and user-friendly design, resulting in a resource that is comprehensive, clear, and effective.
Keywords: InDesign. (Computer file),Desktop publishing,Kỹ thuật in ấn